Gender-Related Differences in Clinical Characteristics and Outcomes of Premature Coronary Artery Disease: Insight from the FOCUS Registry - Ya’nan Qu; Ji’e Yang; Feng Zhang; Chenguang Li; Yuxiang Dai; Hongbo Yang; Yang Gao; Yueyi Pan; Kang Yao; Dong Huang; Hao Lu; Jianying Ma; et al. (Journal of Interventional Cardiology)
Introduction. Although coronary artery disease (CAD) presentations and clinical outcomes differ by sex, little is known about premature CAD (PCAD). The present analysis aimed to evaluate the gender-related differences of PCAD in an Asian population from the FOCUS registry. Methods. A total of 1397 Asian young patients with angiographically confirmed CAD undergoing drug-eluting stent implantation were included in this analysis and divided into two groups according to the genders. Patients were followed up for three years and clinical outcomes were compared between groups. Results. Young women were older and more likely to have hypertension and diabetes than men (all p<0.001). In contrast, males with PCAD had higher BMI and higher prevalence of current smoking as well as previous vessel revascularizations (all p<0.05). Men were more likely to be manifested as total occlusive lesions (p<0.001). Regardless of the clinical characteristics, the cumulative incidences of adverse events such as major adverse cardiovascular event (MACE), cardiovascular death, and all-cause death were not significantly different at one- or three-year follow-up (all p>0.05). Conclusion. Despite remarkable differences in clinical characteristics between Asian males and females with PCAD, the two groups did not differ significantly in clinical outcomes.